Faktor-Faktor Risiko Kepatuhan Dengan Pengobatan Pasien Hipertensi di Rs Wilayah Jawa Barat : Literature Review Article - Dinar Salma Putri Utami; Shania Nurshazidah; Dissa Ayu Putri Andini; Gina Desfina Wijaya; Maya Arfania (Peneliti.net, 2023)
Compliance is one of the factors that determines the success of treatment, especially for people with hypertension which is a silent killer or Non-Communicable Disease, as we know that compliance with hypertension treatment in Indonesia still shows a low rate. Reviewing articles on what factors influence the level of medication adherence in hypertensive patients in hospitals in the West Java region. The data were obtained from electronic databases namely Google Scholar, PubMed, Media Neliti, Researchgate.Net, Sinta Kemendikbud, and Science Direct. The current literature study resulted from 12 articles that met the inclusion and exclusion criteria. Based on the review of the article, it is known that there are factors regarding adherence to treatment of hypertension, namely the use of various drugs, knowledge relations, family support, the role of health workers, provision of drug information, patient motivation, administration of pill cards, demographic characteristics (age, education, occupation), self-motivation, low-salt diet, gender, family history, complications, the experience of obtaining information about hypertension, dietary pattern, family behavior in treating hypertension at home. The existence of family support, high level of knowledge, use of pill cards, the number of drugs consumed by hypertension sufferers, the role of health workers, respondents who do not work, and high motivation to seek treatment have an effect on adherence to treatment of hypertensive patients.